Overview of Peripheral Neuropathy Risk Factors in DM Patients at the Padang Bulan Medan Health Center - Rut Cahyani Zebua; Murni Sari Dewi Simanullang; Imelda Derang (International Journal Of Health Science, 2025)
Diabetes Mellitus is a disease characterized by increased blood sugar levels which results in impaired insulin secretion, requiring lifelong treatment. Diabetes mellitus that is not well controlled can cause microvascular complications, namely peripheral neuropathy, Peripheral Neuropathy which is one of the complications of diabetes mellitus. occurs most frequently and can impair quality of life and even lead to amputation. There are several factors that can cause neuropathy, including long suffering from DM, BMI, hypertension, and age. This study aims to determine the risk factors for peripheral neuropathy in DM sufferers at Padang Bulan Health Center. Medan The research design used is descriptive research with cross sectional approach with a population of 974 people. The sampling technique uses Accidental Sampling with a total sample of 91 respondents. The measuring instruments used are Sop IpTT, observation sheets, medical records. The results shows that the duration of diabetes is > 5 years (59.3%), BMI is 25-29.9 kg/m2 (50.5%), hypertension (67%), elderly >56 years (86.8%). and those experiencing neuropathy (12.1%), it is hoped that the results of this study will provide useful information and knowledge for DM sufferers in preventing neuropathy